Integrasi Pembelajaran Berbasis Masalah dan Konstruktivisme dalam Menumbuhkan Berpikir Kritis Siswa Sekolah Dasar - Verawati (Antroposen: Journal of Social Studies and Humaniora, 2024)
The 21st century demands an educational approach that emphasizes not only declarative knowledge but also the early development of higher-order thinking skills, particularly critical thinking. Unfortunately, learning patterns at the elementary school level are still largely dominated by conventional approaches that position students as passive recipients. This study aims to explore in depth the integration of the Problem-Based Learning (PBL) model with constructivist theory to foster critical thinking skills among elementary school students. A qualitative approach with a case study design was employed at SD Negeri 25 Tanjung Kerja, Kapuas Hulu Regency. Data were collected through participatory observation, semi-structured interviews, and document analysis, and analyzed using the interactive model of Miles, Huberman & Saldaña. The findings reveal that the integration of PBL and constructivism significantly enhances students’ abilities in interpretation, evaluation, and logical reasoning. Teachers, acting as facilitators, provide space for open dialogue and scaffolding aligned with students' zones of proximal development. The implications of this study support a transformation in elementary education towards a more active, reflective, and meaningful learning process for the cognitive development of Indonesian children